2003
DOI: 10.3904/kjim.2003.18.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Cytokine Concentration: A Morphological Study of Liver Cirrhosis Induced by Common Bile Duct Ligation in Rats

Abstract: BackgroundLiver cirrhosis is a diffuse hepatic fibrosis and nodule formation. The transforming growth factor-β1 (TGF-β1) and interleukin-10 (IL-10) are very important cytokines in hepatic fibrogenesis. The aim of this study was to examine the relationship between the changes of the serum cytokines and morphological changes following common bile duct ligation in experimental rats.MethodsCommon bile ducts of fifty male Sprague-Dawley rats were ligated and seven male rats were set aside as controls. Five rats eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…15 Histological examination has shown that hepatic lobular areas were gradually replaced by proliferated bile ducts and fibrous tissue, which led to typical biliary cirrhosis in four to eight weeks after BDL. 11 In the current study, compared to the sham-operated rats, BDL rats showed significantly elevated serum concentrations of ALT, AST, ALK-P and total bilirubin, which is consistent with hepatic inflammation and injury elicited by BDL. The albumin level decreased from week 4 after BDL, which also reflects the development of liver cirrhosis with impaired albumin production.…”
Section: Discussionsupporting
confidence: 82%
“…15 Histological examination has shown that hepatic lobular areas were gradually replaced by proliferated bile ducts and fibrous tissue, which led to typical biliary cirrhosis in four to eight weeks after BDL. 11 In the current study, compared to the sham-operated rats, BDL rats showed significantly elevated serum concentrations of ALT, AST, ALK-P and total bilirubin, which is consistent with hepatic inflammation and injury elicited by BDL. The albumin level decreased from week 4 after BDL, which also reflects the development of liver cirrhosis with impaired albumin production.…”
Section: Discussionsupporting
confidence: 82%
“…Histological examination revealed periportal necrosis, portal inflammation, interlobular degeneration, and focal necrosis and fibrosis in the BDL group, whereas UDCA, MT, or their combination provided significant improvements in all histological scores, but portal inflammation scores were the same for all BDL groups. In parallel with the previous reports indicating that the degree of α-SMA stain demonstrates indirectly the extension of fibrosis, α-SMA expression was increased in saline-treated BDL group (25). However, its expression was reduced significantly with the administration of UDCA or MT or their combination.…”
Section: Discussionsupporting
confidence: 77%
“…3), which have been reported to be profibrogenic genes in vivo. [15][16][17][18][19] However, the mechanism involved in regulating the expression α-SMA and TGF-β1 by CQ in our model is still unknown. Nevertheless, CQ administration prevented the activation of most HSCs may partially through the inhibition of autophagy.…”
Section: 12)mentioning
confidence: 99%